Cardiac glycoside cerberin exerts anticancer activity through PI3K/AKT/mTOR signal transduction inhibition. (1st July 2019) - Hossan, Md Shahadat; Chan, Zi-Yang; Collins, Hilary M.; Shipton, Fiona N.; Butler, Mark S.; Rahmatullah, Mohammed; Lee, Jong Bong; Gershkovich, Pavel; Kagan, Leonid; Khoo, Teng-Jin; Wiart, Christophe; Bradshaw, Tracey D.
Abstract: Natural products possess a significant role in anticancer therapy and many currently-used anticancer drugs are of natural origin. Cerberin (CR), a cardenolide isolated from the fruit kernel of Cerbera odollam, was found to potently inhibit cancer cell growth (GI50 values < 90 nM), colony formation and migration. Significant G2/M cell cycle arrest preceded time- and dose-dependent apoptosis-induction in human cancer cell lines corroborated by dose-and time-dependent PARP cleavage and caspase 3/7 activation, in addition to reduced Bcl-2 and Mcl-1 expression. CR potently inhibited PI3K/AKT/mTOR signalling depleting polo-like kinase 1 (PLK-1), c-Myc and STAT-3 expression. Additionally, CR significantly increased the generation of reactive oxygen species (ROS) producing DNA double strand breaks. Preliminary in silico biopharmaceutical assessment of CR predicted >60% bioavailability and rapid absorption; doses of 1–10 mg/kg CR were predicted to maintain efficacious unbound plasma concentrations (>GI50 value). CR's potent and selective anti-tumour activity, and its targeting of key signalling mechanisms pertinent to tumourigenesis support further preclinical evaluation of this cardiac glycoside. Highlights: Cerberin inhibited growth formation, migration and induced apoptosis in cancer cells evident by cleaved-PARP. Cerberin treatment significantly depleted Bcl-2, Mcl-1, PLK-1, c-MYC, STAT-3 and arrested cells in the G2/M cell cycle phase. Cerberin generated significant increases in reactive oxygen species and led to DNA double strand breaks. Cerberin treatment potently inhibited the PI3K/AKT/mTOR signal transduction pathway. Doses of 1–10 mg/kg of cerberin were predicted to maintain unbound plasma concentrations > GI50 values in mice.